2020
DOI: 10.1029/2020gl090161
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Rifting Zone Revealed by a High‐Density Survey on the Southern Margin of the Southern Okinawa Trough

Abstract: Offshore northern Ishigaki-Jima Island, in the southern Okinawa Trough, offers outstanding opportunities to explore the rifting stage of a backarc system. We report the results of integrated marine geological and geophysical surveys with high-density survey lines in this area. We identify a graben bounded by normal faults and extending approximately 59 km in an ENE-WSW direction off-axis of the southern Okinawa Trough. Submarine volcanoes with active hydrothermalism and associated intrusive structures lie in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…1 In contrast to the regions around the rift axes with low b values, high b anomalies (> 1.2), which is a typical feature for active volcanoes (Wiemer and McNutt 1997;Wyss et al 1997;Nanjo et al 2018), are detected around the Ishigaki Knoll and the Hatoma Knoll and south of the Yonaguni Rift. The Ishigaki Knoll and the Hatoma Knoll are thought to be submarine volcanoes based on seafloor bathymetry and seismic reflection images (Watanabe et al 1995;Misawa et al 2020). Arai et al (2017) reported a potential magma chamber ~ 20 km northeast of the Ishigaki Knoll.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 In contrast to the regions around the rift axes with low b values, high b anomalies (> 1.2), which is a typical feature for active volcanoes (Wiemer and McNutt 1997;Wyss et al 1997;Nanjo et al 2018), are detected around the Ishigaki Knoll and the Hatoma Knoll and south of the Yonaguni Rift. The Ishigaki Knoll and the Hatoma Knoll are thought to be submarine volcanoes based on seafloor bathymetry and seismic reflection images (Watanabe et al 1995;Misawa et al 2020). Arai et al (2017) reported a potential magma chamber ~ 20 km northeast of the Ishigaki Knoll.…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura and Kinjo (2018) interpreted that the southward movement may be due to transient aseismic slips induced by dike intrusions in the Okinawa Trough. Watanabe et al 1995;Arai et al 2017;Misawa et al 2020), hydrothermal sites (red stars; Beaulieu and Szafranski 2020) and magmatic intrusions (white triangles; Arai et al 2017). Thin black lines indicate the seismic reflection profiles of YA01 and YA05 (Arai et al 2017).…”
Section: Seismic Activity In the Southern Okinawa Troughmentioning
confidence: 99%
See 1 more Smart Citation